ICT Integration in Student Learning: Perspectives from a Survey Analysis - Siyamoy Ghory; Sayed Hamidullah Hamidi; Mohammad Amir Atee; Quraishi, Tamanna (MultiTech Publisher, 2024)
This study investigates the integration of Information and Communication Technology (ICT) in student learning at Kabul University through a survey-based methodology. The research explores students' perceptions of ICT integration, including its effectiveness, challenges, opportunities, and impact on engagement and academic performance. A sample of 120 students from diverse faculties participated, with representation across two age ranges: 20-25 and 25-30. The survey instrument, administered electronically, assessed various aspects of ICT integration in the learning environment. Following data collection, meticulous analysis of participant responses was conducted, employing statistical techniques such as frequency distributions and percentages. Results revealed diverse perspectives among students regarding the effectiveness of ICT integration and its influence on engagement and academic performance. Figures presented demographic distributions, perceptions of ICT effectiveness, challenges, opportunities, engagement levels, and academic performance influence among participants. The findings contribute valuable insights into the multifaceted nature of ICT integration in student learning at Kabul University, informing educational practices and policies aimed at optimizing technology-enhanced learning environments. This study underscores the importance of considering students' perspectives in the design and implementation of ICT initiatives, emphasizing the need for tailored strategies to address challenges and capitalize on opportunities for effective integration.